2021
DOI: 10.21873/anticanres.14980
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Renin–angiotensin System Inhibitors on the Efficacy of Anti-PD-1/PD-L1 Antibodies in NSCLC Patients

Abstract: Background/Aim: The Renin-Angiotensin system (RAS) induces immunosuppression in the tumor microenvironment, and RAS inhibitors (RASi) improve the tumor immune microenvironment. We evaluated the impact of RASi on the efficacy anti-programmed cell death-1/Ligand-1 (anti-PD-1/PD-L1) antibodies. Patients and Methods: This retrospective study analyzed non-small cell lung cancer (NSCLC) patients who received anti-PD-1/PD-L1 antibodies monotherapy as second-or later-line treatment. We classified patients into those w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…2.2 months without; HR = 0.59, p=0.008), and while there was a trend towards OS improvement, statistical significance was not achieved (OS = 22.6 months with vs . 14.7 months without; HR = 0.71, p=0.131) ( 32 ). The remaining studies reported a non-significant trend towards improved ICI efficacy with ARB use [Failing et al., 2016 ( 38 ): ORR = 38% with vs 28% without; OR = 2.01, p=0.22; Cortellini et al., 2020 ( 37 ): ORR = 42.9% with vs .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2.2 months without; HR = 0.59, p=0.008), and while there was a trend towards OS improvement, statistical significance was not achieved (OS = 22.6 months with vs . 14.7 months without; HR = 0.71, p=0.131) ( 32 ). The remaining studies reported a non-significant trend towards improved ICI efficacy with ARB use [Failing et al., 2016 ( 38 ): ORR = 38% with vs 28% without; OR = 2.01, p=0.22; Cortellini et al., 2020 ( 37 ): ORR = 42.9% with vs .…”
Section: Resultsmentioning
confidence: 99%
“…This ultimately leads to increased tumor plasticity and therapeutic resistance ( 29 – 31 ). Furthermore, the use of ACEi/ARBs may alter the TME through activating CD4 T cells, NK cells, and altering immunocytokines ( 28 , 32 , 33 ). However, some have demonstrated negative effects on the TME including enhanced M2 differentiation and activated mast cells, raising concerns about concurrent ACEi/ARB and ICI use ( 31 , 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is scientific plausibility to support the potential for a beneficial effect of RAAS inhibitors in patients on an ICI. However, there are limited clinical data on the effect of RAAS inhibitors on outcomes among patients treated with an ICI [ 15 , 16 ]. Given the potentially significant impact on public health of these low-cost and relatively safe interventions, we performed a retrospective cohort study to evaluate the effect of the concurrent use of ICI and RAAS inhibitors in a large cohort of patients with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The PD-1 and PD-L1 axis is a momentous member of this family, which can induce and maintain immune tolerance in external tissues under normal conditions. It has a positive role in preventing excessive tissue inflammation and also exerts a vital regulatory role in miscellaneous of infectious and autoimmune diseases [ 15 , 16 ]. After PD-1 binds to the ligand PD-L, they involved in the excitation, growth, and apoptosis of T cells and restrain the immunological response mediated by T cells.…”
Section: Discussionmentioning
confidence: 99%